They made us happy Betty Comden & Adolph Green's musicals & movies - Propst, Andy 1965- (Oxford University Press, 2019)
A comprehensive examination of the careers, lives and work of Betty Comden and Adolph Green, 'They Made Us Happy' turns the clock back to the glamorous world of Broadway and Hollywood of the 1930s through 1950s, examining the creation of such shows as 'On the Town' and 'Wonderful Town' and such movies as 'Singin' in the Rain' and 'The Band Wagon'
Previously issued in print: 2019. - Includes bibliographical references and index
Keywords: Comden, Betty; Green, Adolph; Green, Adolph -- 1914-2002; Comden, Betty -- 1915-2006; Geschichte; Lyricists / United States; Librettists / United States; Musicals / United States / History and criticism; Musical films / United States / History and criticism; Song; Musical; Film; Text; Drehbuch; USA; Biografie